Adaptation Potential of Teachers of the Third Age in the Conditions of Higher Education Transformation - E. A. Shuklina; M. V. Pevnaya; E. A. Shirokova (Russian State Vocational Pedagogical University, 2020)
Introduction. In many countries around the world, the increase in life expectancy leads to significant social transformations. Institutional structures, social protection policies and legislation on the life and employment of older citizens are being changed today. In Russian higher education, more than a third of professional community belongs to the group of teachers of the third (pre-retirement and retirement) age. The modernisation of this area and the raising of the retirement age will make it possible to study the peculiarities of this group of faculty members as a reserve of the vocational training system.The aim of the present article is to characterise the adaptive potential of social community of teachers of the third age in the context of the transformation of higher education.Methodology and research methods. The methodological framework of the article is based on the set of general scientific approaches: communal, comparative, institutional, resource. The first method provides an opportunity to consider teachers of the third age as a social community with their own specific features. The comparative approach is used to see specific features in dynamics (on the materials of official statistics) and to compare them with similar characteristics of teachers of other age groups. The institutional and resource approaches are aimed at identifying adaptive abilities of teachers of the third age against the background of current restructuring processes in higher education. The article is based on the materials of research projects conducted in 2017-2019 and on a mass survey of teachers. The general population consisted of 51 universities of the Ural Federal District. The volume of the sample of teachers is 810 people.Results and scientific novelty. The study showed that teachers of the third age are characterised by a high level of adaptation to changes in higher education. They successfully fulfill themselves in scientific and pedagogical activities. They are characterised by relatively high publication and grant activities, realisation of new educational forms and high motivation and readiness to improve their com petencies and qualifications. At the same time, teachers of the third age estimate their social security in the professional sphere as extremely low. This community is characterised by a high level of criticality in relation to the implemented institutional changes in the field of higher education, which is based on a socially mature responsibility formed within their professional activities for the consequences of decisions taken.Practical significance. The research undertaken demonstrates the stereotype inadequacy concerning non-adaptability of third-age university teachers to technological, content and organisational innovations. Moreover, teachers of the third age are a significant factor in the sustainable development of universities. Therefore, it is necessary to develop management models and create institutional conditions for maximum use of human capital of third-age teachers, whose peculiarities, needs and opportunities in the system of Russian higher education are inadequately taken into account today.